1997
DOI: 10.1016/s1010-7940(96)01003-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early degeneration of allografts in pulmonary circulation

Abstract: The use of pulmonary allografts, avoidance of relatively short and small conduits of < 14 mm in diameter, might improve the durability of allografts in infants and small children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…Late death and dysfunction of the pulmonary homograft were assessed with more emphasis [2,3,[5][6][7][10][11][12]. In our study, hospital mortality was 18%, in accordance with the literature, on which mortality ranges from 6% to 27% [2.5-10].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Late death and dysfunction of the pulmonary homograft were assessed with more emphasis [2,3,[5][6][7][10][11][12]. In our study, hospital mortality was 18%, in accordance with the literature, on which mortality ranges from 6% to 27% [2.5-10].…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have focused on hospital mortality for surgical repair of the obstructive diseases of the right heart, citing only its rate, but rather than assessing the risk factors [5][6][7][8][9][10]. Late death and dysfunction of the pulmonary homograft were assessed with more emphasis [2,3,[5][6][7][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have found no difference in efficacy between the aortic and pulmonary homograft, 21,25 most have supported the superiority of the latter. [22][23][24] Accordingly, we preferentially used pulmonary homografts in the present series. As a result, because there were so few patients with aortic homograft implantation, the present study does not resolve the issue of which homograft type is preferable.…”
Section: Discussionmentioning
confidence: 99%
“…All kinds of conduits have some disadvantages such as degeneration or lack of growth potential through time. [5] Contegra results vary in reports, although long-term complication is usually conduit stenosis which is mostly seen in smaller diameter conduits. [6,7] Dilatation of the Contegra conduit is rare.…”
mentioning
confidence: 99%